Strategi Pemasaran Sebagai Upaya untuk Meningkatkan Produktivitas UMKM di Desa Sambiharjo Kecamatan Paranggupito - Sri Yuliani; Maulana Al Ghifari; Albanna Sayf Aladl; Aly Farhan; Jeremy Farrel Pratama; Agnes Ardiani; Indira Hapsari Estiningtyas; Melania Ika Wardani; Regina Dewitri; Verensia Juan Akyani; Zain Afdha Zulaechah (CV. Ulil Albab Corp, 2023)
MSMEs have an important contribution to the growth and development of the Indonesian economy. However, there are many problems faced by MSMEs, one of the aspects of poor marketing. The lack of marketing aspects occurred in MSMEs in Sambiharjo Village, Paranggupito District, Wonogiri Regency. So a marketing strategy is needed with the aim of increasing the productivity of MSMEs and increasing the economic value of MSME actors through updating and improving the marketing aspects of MSMEs.The method used to improve marketing strategy are interviews, explanation, discussion, and practices. Activities to marketing strategies applied adjust by deprivation and for businesses covering every product packaging, products photos, branding the product, and digital marketing. The development of micro and small scale business strategy that has already been done will be monitored through social media to sustainable. Exposure and training related to marketing strategies is expected to provide the ability to a small and medium enterprises actors to carry out marketing strategies well independently. In addition, this activity can have an impact on the progress of MSMEs, especially in rural areas, which have limitations both in terms of capital and access to marketing.